BACTERIOLOGIGAL AND GENETIC STUDY OF Pseudomonas aeruginosa ISOLATES - M. Tawfiq, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
Fifty P. aeruginosa isolates were isolated from patients suffered of wound, ear and chronic pulmonary infections to assess the presence of nan1 and nan2 genes .P. aeruginosa isolates were 10(20%) from chronic pulmonary infection ,20(40%) from each of ear and wound infections. isolates exhibted highly sensitivity to (Cefepime ,Meropenem ,Azitheromycin) and version resistance to Cefotaxime, Gentamicin, Ceftazidim ,Clorithromycin, Tobramicin,Ciprofluxacin In percentages (70% ),(60%) ,(50%), (40%) , (36%) and(34%) respectively.Seventeen isolates were choosen to searching nan1 and nan2 genes by PCR technique depending on the resist to four groups of antibiotics (Aminoglycoside,Third generation of beta-lactam ,quinolones ,Macrolides , (29.4%) possess both genes.nan1 were distributed in(41.2%) in percentages (50%) for each of wound and ear isolates and (20%)for chronic pulmonary isolates,while nan2 was dissemination (70.6%) in percentages100%, 66.6% and 50% for chronic pulmonary, ear and wound isolates respectively In conclusion, these data suggest that the prevalence of nan2 in all infections ,that suggest apossible role of this gene in disease evolution especially in pulmonary patients while nan1 was low prevalence in isolates may be related to infection site.